Steroid use for established bronchopulmonary dysplasia: study protocol for a systematic review and meta-analysis - Roy K Philip; Joanna Seliga-Siwecka; Eduardo Villamor; Maria Pierro; Niazy Al Assaf; Sabina Strashun; Roberto Chioma; Kinga Zielińska; Krzysztof Włodarczyk (BMJ Open)
Introduction Postnatal steroids during the first few weeks of life have been demonstrated to be effective in decreasing the incidence of bronchopulmonary dysplasia (BPD), a serious chronic respiratory condition affecting preterm infants. However, this preventive option is limited by the concern of neurological side effects. Steroids are used to treat established BPD in an attempt to reduce mortality, and length of stay and home oxygen therapy, both of which associated with high levels of parental stress and healthcare costs. Moreover, a late timing for steroid treatment may show a more favourable safety profile in terms of neurodevelopment outcomes, considering the added postnatal brain maturation of these infants. Here, we report a protocol for a systematic review, which aims to determine the efficacy and long-term safety of postnatal steroids for the treatment of established BPD in preterm infants.Methods and analysis MEDLINE, Embase, Cochrane databases and sources of grey literature for conference abstracts and trial registrations will be searched with no time or language restriction. We will include case–control studies, cohort studies and non-randomised or randomised trials that evaluate postnatal steroids for infants diagnosed with moderate or severe established BPD at 36 weeks’ postmenstrual age. We will pool data from studies that are sufficiently similar to make this appropriate. Data extraction forms will be developed a priori. Observational studies and non-randomised and randomised clinical trials will be analysed separately. We will combine OR with 95% CI for dichotomous outcomes and the mean difference (95% CI) for continuous outcomes. We will account for the expected heterogeneity by using a random-effects model. We will perform subgroup analysis based on the a priori determined covariate of interest.Ethics and dissemination Systematic reviews are exempted from approval by an ethics committee. Attempts will be sought to publish all results.PROSPERO registration number CRD42021218881.